Role of fumigation in labour conditions characteristic of the grain transport conveyor workers = Роль фумигации в характеристике условий труда рабочих зернового транспортного конвейера - Shafran, L. M.; Sidorenko, S. G.; Golikovа, V. V.; Zukow, W. (Journal of Education, Health and Sport, 2015)
Shafran L. M., Sidorenko S. G., Golikova V. V., Zukow W. Role of fumigation in labour conditions characteristic of the grain transport conveyor workers = Роль фумигации в характеристике условий труда рабочих зернового транспортного конвейера. Journal of Education, Health and Sport. 2015;5(10):350-362. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.45341 http://ojs.ukw.edu.pl/index.php/johs/article/view/3355 https://pbn.nauka.gov.pl/works/709979 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.09.2015. Revised 25.10.2015. Accepted: 31.10.2015. UDC - УДК 613.6+616-099-057:656.6-083 ROLE OF FUMIGATION IN LABOUR CONDITIONS CHARACTERISTIC OF THE GRAIN TRANSPORT CONVEYOR WORKERS РОЛЬ ФУМИГАЦИИ В ХАРАКТЕРИСТИКЕ УСЛОВИЙ ТРУДА РАБОЧИХ ЗЕРНОВОГО ТРАНСПОРТНОГО КОНВЕЙЕРА L. M. Shafran*, S. G. Sidorenko**, V. V. Golikova*, W. Zukow*** Л. М. Шафран, С. Г. Сидоренко, В. В. Голикова, В. Жуков *Ukrainian Scientific and Research Institute of Transport Medicine, Odessa, Ukraine **Main State Sanitary and Epidemiological Service in Kirovograd region of Ukraine ***Kazimierz Wielki University, Bydgoszcz, Poland Abstract Complex investigations of working conditions of specialists, involved in the export of grain in Ukraine at all stages of the transport conveyor (elevators - freight transport - rail - enterprises for the primary processing of grain and seeds - grain terminals at sea and river ports - ships for grain transportation in bulk (bulkers)) is made. Under supervision there were 755 people, males, aged 27-56 years, with the occupational experience 3-35 years. All workers were divided into 6 groups: 1.- workers of elevators and grain terminals; 2 - workers of the enterprises for processing of grain and seeds; 3. - workers of fodder industries; 4. – truck drivers; 5 - specialists of fumigation units; 6 – workers without any contact with grain cargoes, control. The research included: analysis of occupational activities by professiografic methods (multimoment observations and self-made checking of working operations and time), assessment of hazards in the volume requirements for certification of workplaces (microclimate parameters, noise, vibration, the definition of dust, germs and fungi, chemicals in the air, including phosphine, indicators of severity and intensity of labor), the study of morbidity with temporary disability according to the company’s data and symptoms of health disorders mentioned in a specially designed questionnaire. The results showed that the surveyed workers are exposed to general and specific hazards types of the working environment. It established the important role of residual amounts of phosphine and airborne dust generated during overload, moving under fumigation of grain and seeds at grain elevators, port terminals, as well as containing the germs and fungi bioaerosol as sources of harmful effects on the operators and truck drivers, which plays an important role in the etiology and pathogenesis of occupationally caused diseases in participants of grain transport conveyer. Concentrations of vegetable dust in grain elevators and terminals exceed the permissible exposure limit (4 mg / m3) in 2-6 times, and the phosphine concentration in the breathing zone of fumigation specialists - up to 15 times. The surveyed groups of workers also greatly differ in severity and intensity of labor. On the basis of integrated work assessment of elevators, grain terminals personnel and specialists in fumigation assigned to class 3.2, animal feed mills workers of and truck drivers – to class 3.1, and workers of the enterprises for processing of grain and seeds - to the 3.1 - 2nd classes in accordance with the current hygienic classification. It is designed and implemented a range of preventive measures to improve working conditions and of the health preservation of workers the grain transportation conveyor. Further researches are needed to differentiate hygienic assessment of employees grain processing industries and the transport conveyor. The necessity for correction of grain dust PEL considering content of not deposited fractions of pesticide residues primarily fumigants. Keywords: grain, transportation, fumigation, phosphine, workers, working conditions. Streszczenie ROLA FUMIGACJI W CHARAKTERYSTYCE WARUNKÓW PRACY RUROCIĄGU DO TRANSPORTU ZBÓŻ. Kompleksowe badania warunków pracy zaangażowanych w eksport zboża na Ukrainie na wszystkich etapach przenośnika transportu (windy - transportu towarowego - kolejowe - przedsiębiorstwa do pierwotnej obróbki zbóż i nasion - terminale zbożowe w portach morskich i rzecznych - statki do przewozu luzem ziarna (bulkers)). Pod obserwacją były 755 osoby, mężczyźni w wieku 27-56 lat, z doświadczeniem w zawodach studiował 3-35 lat. Wszyscy badani zostali podzieleni na 6 grup: 1 - pracownicy windy roboczych i terminali zbożowych; 2 - pracownicy przedsiębiorstw do przetwórstwa zboża i nasion; 3 - pracownicy RSS gałęzi przemysłu; 4 - kierowcy ciężarówek; 5 - eksperci w fumigacji; 6 – pracownicy nie kontaktujący się z ładunkiem zboża, kontroli. Badaniami objęto: analiza działań produkcyjnych professjograficznych metod multimomentnych obserwacji i samofotografii czasu pracy, ocena zagrożeń w wymogami głośności dla certyfikacji zakładów pracy, badania zachorowalności o czasowej niezdolności do pracy, zgodnie z firm i objawów zaburzeń zdrowia specjalnie zaprojektowany kwestionariusz. Wyniki wykazały, że badani eksperci są narażone na ogólnych i szczególnych zagrożeń w środowisku pracy. Ustalono ważną rolę resztkowych ilości fosfinie i unoszącego się w powietrzu pyłu wytwarzanego podczas przeciążenia, przemieszczają się w ramach fumigacji ziarna i nasion w elewatorów zbożowych, terminalach portowych, a także zawierający bakterie i grzyby bioaerozolu jako źródeł szkodliwego wpływu na operatorów i kierowców pojazdów, który odgrywa ważną rolę w etiologii i patogenezie chorób spowodowanych u pracowników profesjonalnych ziarnotransportowych rurociągów eksportowych. Stężenia pyłu roślin w elewatorach zbożowych i ziarnoterminalach przekraczały maksymalnego dopuszczalne (4 mg / m3) w 2-6 razy, a stężenie fosfina w strefie oddychania odpowiedniej fumigacji - do 15 razy. Grupy pracowników ankietowanych również znacząco różniły się w nasileniu i intensywności pracy. Na podstawie zintegrowanej oceny pracy ekspertów w fumigacji przypisane do klasy 3.2, pracownicy elewatorów zbożowych, terminale zboża, produkcji pasz, kierowcy ciężkich pojazdów - do klasy 3.1 i pracownicy przedsiębiorstw do przetwórstwa zbóż i nasion - do 3,1-2.0 klasom obecnej klasyfikacji higienicznej. Zaprojektowaliśmy i wdrożyliśmy szereg środków mających na celu poprawę warunków pracy i ochronę zdrowia pracowników ziarnotransportowego przenośnika. Konieczne są dalsze badania, aby odróżnić ocenę higieniczną przemysłu przetwórstwa zboża i pracownicy rurociągu transportowego. Konieczność korekty RPP ziarna pyłu biorąc pod uwagę jej treść zawisu i frakcji pozostałości pestycydów głównie fumigacji. Słowa kluczowe: zboża, transport, odgrzybianie, fosfin, pracownicy, warunki pracy. Реферат Проведены комплексные исследования условий труда работников, участвующих в операциях по экспорту зерна в Украине на всех этапах транспортного конвейера (элеваторы – грузовой автотранспорт – железнодорожный транспорт – предприятия по первичной переработке зерна и семян – зерновые терминалы в речных и морских портах – суда для перевозки зерна насыпью (балкеры)). Под наблюдением находилось 755 человек, лица мужского пола, в возрасте 27-56 лет, со стажем работы в изучаемых профессиях 3-35 лет. Все обследуемые были разделены на 6 групп: 1.- рабочие элеваторов и зерновых терминалов; 2. – работники предприятий по переработке зерна и семян; 3. – работники комбикормовых производств; 4. – водители грузовых автомобилей; 5. – специалисты по фумигации; 6 – не контактирующие с зерновыми грузами, контроль. Исследования включали: профессиографический анализ производственной деятельности методами мультимоментных наблюдений и самофотографии рабочего времени, оценка вредных и опасных факторов в объеме требований к аттестации рабочих мест, изучение заболеваемости с временной утратой трудоспособности по данным предприятий и симптоматики нарушений в состоянии здоровья по специально разработанным анкетам. Результаты исследований показали, что обследованные специалисты подвергаются действию общих и специфичных вредных факторов производственной среды. Установлена важная роль остаточных количеств фосфина и витающей пыли, образующейся при перегрузке, перемещении фумигированного зерна и семян на элеваторах, портовых терминалах, а также содержащего микробы и грибы биоаэрозоля, как источников вредного воздействия на организм операторов и водителей автотранспорта, что играет важную роль в этиологии и патогенезе профессионально обусловленной заболеваемости участников экспортного зернотранспортного конвейера. Концентрации растительной пыли на элеваторах и зернотерминалах превышали предельно допустимые (4 мг/м3) в 2-6 раз, а концентрации фосфина в зоне дыхания специалистов по фумигации – до 15 раз. Группы обследованных рабочих существенно отличались также по тяжести и напряженности труда. На основе интегральной оценки труд работников элеваторов, зерновых терминалов, специалистов по фумигации отнесен к классу 3.2, комбикормового производства, водителей большегрузных автомобилей – к классу 3.1, а работников предприятий по переработке зерна и семян – к 3.1-2-му классам по действующей гигиенической классификации. Разработан и внедрен комплекс мероприятий по оздоровлению условий труда и сохранению здоровья работников зернотранспортного конвейера. Необходимы дальнейшие исследования по дифференциации гигиенической оценки труда работников зерноперерабатывающих производств и транспортного конвейера. Показана необходимость коррекции ПДК зерновой пыли с учетом содержания в ней витающих фракций и остаточных количеств пестицидов, прежде всего, фумигантов. Ключевые слова: зерно, транспорт, фумигация, фосфин, рабочие, условия труда.